أستاذ المدرسة الابتدائية - سلامي, دلال (جامعة الوادي - University of Eloued, 2022)
الأستاذ الناجح هو من تكتمل عنده المادة العلمية والكفايات التدريسية بالفهم الصحيح لسلوكيات المتعلمين بحيث يوازن بين حق الطفل للاستمتاع بطفولته وبين حقه في التعليم الذي ينميّه. إن الأستاذ في المدرسة الابتدائية الجزائرية الحديثة يعاني من مشاكل كثيرة تعوقه لتحقيق الأهداف التربوية فمن خلال هاته الورقة البحثية نحاول الإجابة عن الأسئلة التالية: ما هي أهم المشاكل التي تعوق عمل أستاذ المدرسة الابتدائية؟ - كيف يمكن الاستفادة من تجارب بعض الدول الرائدة في التعليم لتحسين أداء الأستاذ ؟ وقد خلصت هذه الورقة البحثية إلى انه هناك نقاط مهمة ومهمة جدا وهي مشتركة في تجربة اليابان وفنلندا وكوريا لو أخذت بالاهتمام المطلوب لحلت أغلب المشاكل في المدرسة الابتدائية الجزائرية الكلمات المفتاحية: أستاذ - مدرسة الابتدائي Abstract : A successful teacher is the one who has acquired the academic element and teaching competencies accomplished with a correct understanding of learners' behaviors and needs so that it makes a balance between the child's right to enjoy his childhood and his right to learning which develops him. The teacher in the modern Algerian primary school suffers from many problems that hinder him in achieving educational goals. Through this research paper, we try to answer the following questions: -What are the most important problems hindering the work of an primary school teacher? - How can we benefit from the experiences of some of the leading education countries to improve teacher performance?
The primary school teacher - Reality and prospects
مقال
Keywords: أستاذ ، مدرسة الابتدائي; teacher, Elementary school.